Flavian Responses to Nero's Rome - Heerink, Mark; Meijer, Esther (Amsterdam University Press, 2022)
In this interdisciplinary volume, a team of classicists, historians, and archaeologists examines how the memory of the infamous emperor Nero was negotiated in different contexts and by different people during the ensuing Flavian age of imperial Rome. The contributions show different Flavian responses to Nero's complicated legacy: while some aspects of his memory were reinforced, others were erased. Emphasizing the constant and diverse nature of this negotiation, this book proposes a nuanced interpretation of both the Flavian age itself and its relation to Nero's Rome. By combining the study of these strategies with architectural approaches, archaeology, and memory studies, this volume offers a multifaceted picture of Roman civilization at a crucial turning point, and as such will have something to offer anyone interested in classics, (ancient) history, and archaeology.